Implementing an Evidence‐Based Fall Prevention Program in an Outpatient Clinical Setting. Issue 12 (28th October 2013) - Li, Fuzhong; Harmer, Peter; Stock, Ronald; Fitzgerald, Kathleen; Stevens, Judy; Gladieux, Michele; Chou, Li‐Shan; Carp, Kenji; Voit, Jan
<x xml:space="preserve">Abstract</x> Objectives To investigate the dissemination potential of a Tai Ji Quan–based program, previously shown to be efficacious for reducing risk of falls in older adults, through outpatient clinical settings. Design A single‐group pre/post design in which participants attended a twice‐weekly Tai Ji Quan training program for 24 weeks. Setting Communities in Lane County, Oregon. Participants Independently living individuals (N = 379) aged 65 and older. Measurements Using the Reach, Effectiveness, Adoption, Implementation and Maintenance framework, the primary outcome was the proportion of participating healthcare providers who made referrals. Secondary outcomes were the proportion of referred individuals agreeing to participate and enrolling in the program, and measures of program implementation, maintenance, and effectiveness (on measures of falls, balance, gait, physical performance, and balance efficacy). Results Of the 252 providers invited to participate, 157 made referrals (62% adoption rate). Of 564 individuals referred, 379 (67% reach) enrolled in the program, which was successfully implemented in senior and community centers with good fidelity, 283 completed the program (75% retention), and 212 of these attended 75% or more of the 48 sessions. Participants reported a reduction in falls, with an incidence rate of 0.13 falls per person‐month, and showed significant improvement from baseline in all outcome measures. A 3‐month postintervention follow‐up indicated encouraging levels of program maintenance among providers, participants, and community centers. Conclusion Healthcare providers successfully implemented a protocol to refer individuals at risk of falling to a Tai Ji Quan–based program. The evidence‐based program appears readily scalable and exportable, with potential for substantial clinical and public health effect.